Respiratory Monitoring System Using Plastic Optical Fiber Sensor Based on Internet of Medical Things (IoMT) - Ida Laila; Arifin Arifin (JST (Jurnal Sains dan Teknologi), 2025)
Respiratory disorders remain a major health concern because conventional monitoring systems are often invasive and expensive, which limits their accessibility for long-term use. The demand for non-invasive, low-cost, and reliable respiratory monitoring technologies is increasing, particularly those that can be integrated into smart healthcare systems. This study aimed to design, develop, and evaluate a respiratory monitoring system based on a spiral Plastic Optical Fiber (POF) sensor integrated with Internet of Medical Things (IoMT) technology. The research employed an experimental design with a quantitative approach. The test subject consisted of one adult participant who was assessed under three breathing conditions: normal, fast, and slow. Data were collected using a POF sensor connected to an Arduino Uno, a phototransistor, an XBee module, and a Raspberry Pi, after which the results were visualized. Data analysis was carried out through sensitivity and resolution calculations. The findings showed that the spiral POF configuration with three windings produced the best performance, with voltage amplitudes of 0.220 V (normal), 0.205 V (fast), and 0.186 V (slow). The corresponding sensitivity and resolution values were 0.412 V/s (0.002 s), 0.246 V/s (0.0040 s), and 0.619 V/s (0.0016 s). These results confirm that the developed system is simple to fabricate, cost-effective, highly sensitive, and capable of providing real-time, non-invasive respiratory monitoring. The study concludes that integrating POF-based sensors into the IoMT platform is feasible for application in smart healthcare services. Furthermore, the findings highlight the potential of POF-based respiratory sensors to be developed into affordable health monitoring technologies.